Health promoting properties of protein hydrolysates produced from oil palm (Elaeis guineensis ) kernel - Chang, Sui Kiat; Hamajima, Hiroshi; Ismail, Amin; Yanagita, Teruyoshi; Mohd Esa, Norhaizan; Baharuldin, Mohamad Taufik Hidayat (Korean Society of Food Science and Technology, 2014)
This study aimed to determine the lipid-lowering properties, antioxidant capacity (AC) and angiotensin-I converting enzyme (ACE)-inhibitory activity of oil palm kernel protein hydrolysates (OPKHs) that were produced using protease and pepsin-pancreatin hydrolysis. The effects of the OPKHs on apolipoprotein B (apoB) secretion was assessed using HepG2 cells as a model and the AC of the OPKHs was determined based on ABTS radical scavenging activity and ferric reducing antioxidant power (FRAP). Both protease and pepsin-pancreatin hydrolysates reduced apoB secretion significantly (p<0.05). The OPKHs scavenged ABTS radicals effectively and demonstrated a high reducing power even at a low concentration (1 mg/mL). The AC of the OPKHs was significantly correlated with the OPKHs protein content. However, the OPKHs demonstrated very low ACE-inhibitory activity. The pepsinpancreatin hydrolysate demonstrated significant lipidlowering properties, favourable AC and ACE inhibitory activity in compared to protease hydrolysate. Therefore, OPKH demonstrate the potential as a nutraceutical for functional foods.